SUBSTITUTION MECHANISM OF AL IONS IN MGSIO3 PEROVSKITE UNDER HIGH PRESSURE CONDITIONS FROM FIRST-PRINCIPLES CALCULATIONS - Yamamoto T.; Yuen D.A.; Ebisuzaki T. (My University, 2003)
Large-scale first-principles density functional theory (DFT) calculations have been carried out to investigate how Al3+ can be incorporated into MgSiO3 perovskite under high pressure and to study the resultant change in the compressional mechanism of MgSiO3 perovskite. We examined two types of MgSiO3 models with 6.25 mol% Al2O3: charge-coupled substitution and oxygen-vacancy mechanisms. Five pressure points from 0 to 100 GPa have been considered. At each pressure point, we have calculated five models of the oxygen vacancy and five models of the charge-coupled mechanisms. We also change the internal positions of the substituted Al in the calculated cells, which have 80 atoms. Our free energy calculations show Al3+ replaces the nearest-neighbor cation pairs (Mg2+ and Si4+) at all pressures investigated. The calculated bulk modulus of the most energetically favorable model is 3.4% lower than that of the Al-free MgSiO3 perovskite. These results may have important implications for discriminating between thermal and compositional effects of 1-D Earth models and the possible influence of aluminum perovskite.
Keywords: ALUMINOUS PEROVSKITE; FIRST-PRINCIPLES CALCULATIONS; SUBSTITUTION MECHANISM; BULK MODULUS